Dynamic changes of a city's carbon balance and its influencing factors: a case study in Xiamen, China. Issue 3 (3rd July 2016) - Lin, Tao; Ge, Rubing; Zhao, Qianjun; Zhang, Guoqin; Li, Xinhu; Ye, Hong; Liao, Jiangfu; Yin, Kai
ABSTRACT: Due to rapid urbanization and increasing energy consumption, human society poses increasing pressure on the surrounding ecosystems that it depends on. As a result, evaluation of urban development should view cities as complex ecosystems including human and natural elements. This paper establishes a carbon balance index (CBI) for an urban ecosystem based on its socio-economic development and land use and land cover change in Xiamen, a rapidly urbanizing coastal city in southeast China. Dynamic changes in CBI can quantitatively indicate the sustainability of the urbanization process from a carbon cycling perspective. Results show that Xiamen's carbon balance condition experienced three stages: the period 1987–2002 where CBI decreased slightly, 1992–2002 where CBI moderately increased from 1.4 to 4.2, and 2003–2011 where CBI rapidly increased from 5.2 to 17.3. The carbon imbalance increased with the expansion of urban scale and urbanization. By stepwise multiple regression analysis, it was found that the main influencing factors of CBI are urbanization rate, industrial coal consumption, length of roadway network and forest area, and city managers should take these factors into consideration to achieve low-carbon city development. Finally, the CBI for the year 2030 is predicted based on CO2 emissions and sequestration scenarios.